Review on Wellhead Uplift Phenomenon in Offshore Thermal Recovery Wells - Sun, Zetao (Scientific Journal of Technology, 2026)
With the continuous rise in global energy demand and the gradual depletion of onshore conventional oil and gas resources, the development of offshore heavy oil resources has become a key strategic direction for the petroleum industry. Heavy oil reserves account for a relatively high proportion of total oil reserves in China’s Bohai Sea area. This type of resource is characterized by high viscosity and poor fluidity, resulting in extremely low recovery rates with conventional mining technologies. Therefore, cyclic steam stimulation (CSS) is widely used as the mainstream thermal recovery technology. This technology heats the formation by periodically injecting high-temperature steam to reduce the viscosity of heavy oil, thereby achieving efficient recovery. However, during this process, the wellbore is subjected to severe thermal cycling, causing significant thermal expansion of the casing string due to high temperatures, which in turn triggers wellhead uplift. Field data show that the wellhead uplift of some offshore thermal recovery wells has reached a relatively high level, which not only threatens the integrity of wellhead seals, subsea connections, and riser systems but also poses a serious hazard to the overall safety of the platform. It may even lead to production interruption and huge economic losses. Therefore, in-depth research on the relevant mechanisms, prediction methods, and prevention and control measures of wellhead uplift in offshore thermal recovery wells is of great engineering significance and practical value for ensuring the safe and efficient development of offshore heavy oil.